Financial Performance Analysis of PT. Bank BPD Daerah Istimewa Yogyakarta During Pandemic - Maria Regina Nansi (Enrichment : Journal of Management, 2022)
Financial analysis is used as a benchmark for assessing the performance of a bank where from this financial report information on its financial position will be obtained, so that external parties can use it to determine the risks to a bank. This research investigates the performance of BPD DIY during the pandemic through analysis of financial ratios such as Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Return On Assets (ROA), Return On Equity (ROE), Operating Ratio (OR), and Loan to Deposit Ratio (LDR). The study found that the performance of BPD DIY in the midst of deteriorating macroeconomic conditions due to the pandemic is good in terms of financial ratio proxies. Banks must always carry out internal evaluations on an ongoing basis to improve bank capabilities and minimize risk. E